2016
DOI: 10.1021/acs.jafc.6b04011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Identification, and Quantification of Residues after Treatment of Ready-To-Eat Salami with 36Cl-Labeled or Nonlabeled Chlorine Dioxide Gas

Abstract: When ready-to-eat salami was treated in a closed system with Cl-labeled ClO (5.5 mg/100 g of salami), essentially all radioactivity was deposited onto the salami. Administered ClO was converted to Cl-chloride ion (>97%), trace levels of chlorate (<2%), and detectable levels of chlorite. In residue studies conducted with nonlabeled ClO, sodium perchlorate residues (LOQ, 4 ng/g) were not formed when reactions were protected from light. Sodium chlorate residues were present in control (39.2 ± 4.8 ng/g) and chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Regardless of the target food, chlorine dioxide was released from the reaction vessel in sufficient quantities to accumulate in the reaction chamber, indicating that excess gas was present with respect to the absorptive capacity of each food within the constraints of the exposure period. In a similar study using sliced, pealed, readyto-eat salami, 7 gaseous chlorine dioxide concentrations rose during the initial 15 min of the experiment, but thereafter decreased until the gas concentration fell to near background levels at 120 min. Radioactivity recovered on the salami indicated that the salami had a very high capacity to absorb and retain the gas, likely because of the high moisture content of salami and the high absorptive surface area of the sliced salami.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Regardless of the target food, chlorine dioxide was released from the reaction vessel in sufficient quantities to accumulate in the reaction chamber, indicating that excess gas was present with respect to the absorptive capacity of each food within the constraints of the exposure period. In a similar study using sliced, pealed, readyto-eat salami, 7 gaseous chlorine dioxide concentrations rose during the initial 15 min of the experiment, but thereafter decreased until the gas concentration fell to near background levels at 120 min. Radioactivity recovered on the salami indicated that the salami had a very high capacity to absorb and retain the gas, likely because of the high moisture content of salami and the high absorptive surface area of the sliced salami.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Sealed chambers were the same as described by Smith et al , Briefly, sanitations occurred within a 5.5 L sealable glass tank (11 × 22 × 23.5 cm; W × L × D), which was completely wrapped in aluminum foil to protect the chamber contents from laboratory light. Experimental tanks were placed onto a magnetic stirring plate, and eggs or fruit were placed onto a slotted glass pedestal within each tank.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations